2021
DOI: 10.3389/fpsyg.2021.569115
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distance Toward Air Pollution and Purchase Intention for New Energy Vehicles: An Investigation in China

Abstract: Air pollution in China has been drawing considerable attention in recent years. The emergence of new energy vehicles (NEVs) provides hope to reduce air pollutant emission. However, consumers' recognition and acceptance of NEVs remain at the early stage. This research aims to explore how consumers' environmental concern influences their NEV purchase intention. Specifically, this research conducted an online survey and an experiment to address the following issues: (1) how consumers' psychological distance (PD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 61 publications
(103 reference statements)
0
17
0
Order By: Relevance
“…The media environment is another potential driver of the formation of climate change opinion. The Construal Level Theory suggests that psychological distant concepts like climate change are usually represented by high‐level and abstract concepts and heavily determined by media exposure (Liu et al., 2021; Maiella et al., 2020). The Chinese media coverage of climate change focuses on environmental and human impacts but is hesitant to include any conflicting views (Han et al., 2017), as it happens daily in Western countries (Gustafson et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The media environment is another potential driver of the formation of climate change opinion. The Construal Level Theory suggests that psychological distant concepts like climate change are usually represented by high‐level and abstract concepts and heavily determined by media exposure (Liu et al., 2021; Maiella et al., 2020). The Chinese media coverage of climate change focuses on environmental and human impacts but is hesitant to include any conflicting views (Han et al., 2017), as it happens daily in Western countries (Gustafson et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, people's satisfaction has been closely related to risk factors such as confirmed cases and deaths per million [48]. In contrast, according to Liu et al [27], consumers' RP of air pollution's consequences mediates between PD and intended action as a kind of acceptance.…”
Section: Hypothesis 2-6 (H2-6) Pd Is Positively Associated With Rpmentioning
confidence: 99%
“…This degree of PD's proximity and specificity is linked to the receptivity of the specific object concerned [26]. For example, Liu et al [27] demonstrated that when risk perception of air pollution's consequences plays a considerable mediating role in inducing purchase intention for new energy vehicles, consumers' PD toward air pollution has a significant effect. Furthermore, Tan et al [28] showed that different dimensions of PD (e.g., social, temporal, uncertainty, and experiential) might explain local acceptance of shale gas development in China.…”
Section: Study 1: Knowledge Calibration (Kc) With Psychosocial Distance (Pd) On Nuclear Energy Policy Satisfaction (Ps)mentioning
confidence: 99%
“…(3) Since 2015, relevant studies have begun to focus on sustainable development and evaluating the impact of planned behavior theory and psychological distance theory on citizen environmental behavior. The planned behavior theory states that human behavior is the result of deliberate planning, which includes five elements: attitude, subjective norms, perceived behavior control, behavior intention, and behavior (Liu et al, 2021;Reijonen et al, 2021). With the acceleration of industrialization, an increasing number of countries and individuals have begun to realize that "lucid waters and lush mountains are invaluable assets" and thus have integrated a sustainable development strategy into their own development process.…”
Section: Analysis Of Evolution Trendmentioning
confidence: 99%